Speech behavior of women characters in representation of the concept FAMILY in in the dramaturgical discourse of Wendy Wasserstein - Ostropalchenko, Yu. (Studia Philologica, 2021)
The article is devoted to the study and systematization of the speech behavior of women in the representation of the concept FAMILY in the communicative space of the characters of the modern American dramatic discourse on the example of the plays of Wendy Wasserstein. The dynamics of gender markers reveals trends in the cognitive system in the axiological paradigm of American dramatic discourse. Communicative practices of the characters of dramatic works reflect the stereotypical behavior of male and female characters in different situations, which allows to study the specifics of female and male language behavior of a particular society. In studying this specificity, researchers often turn to linguoconceptology. Studies of the subject’s linguistic behavior in line with the anthropocentric paradigm allow linguists to study the processes occurring at the time of the creation of a linguistic phenomenon, which reflects cultural, gender, social and age factors. Any of the listed aspects affects the communication strategies of the subject, which makes it possible to study the linguistic activity of the broadcaster from the point of view of linguocultural, conceptual and gender approaches. Conceptual fields based on replicas of female characters in modern plays by American playwright Wendy Wasserstein are analysed. Communicative strategies of speech behavior of female characters in dramatic discourse indicate the linguistic and cultural features of the language of communicators, which suggests the existence of a unique language culture of American society, which was formed under the influence of accepted norms in society. The main concepts of the playwright’s discourse “Family” and “Career”, which are verbalized through a number of examples, are analysed.